A Validity of E-LKPD Based on Problem Based Learning for Improve Critical Thinking Skill - Meitaza, Dariah; Sriyanti, Ida; Marlina, Leni; Zulkarnain, Nur Najihah Binti (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This study aims to determine the validity of the developed E-LKPD. Methodology: The data obtained from the experts were analyzed by considering comments or suggestions using the Content Validity Ratio (CVR) and Content Validity Index (CVI). This E-LKPD product validation sheet was validated by 7 experts, namely 2 lecturers from the Malaysian University of Technology, 2 lecturers from Sriwijaya University, 2 junior high school teachers, and 1 Laboratory Practitioner. This product is validated in the aspects of design, content, Problem Based Learning, and aspects of students' critical thinking skills. Main Findings: The results of the validity of the E-LKPD conducted by 7 validators are allowed to be used. because the overall value of the E-LKPD aspect (S-CVI / AVE) is 0.95 and falls into the category of a very strong level of validity. while the S-CVI /UA score is 1 so that it can prove this product can be used for teaching materials from teaching and can improve students' thinking skills through the problem-based learning model. Novelty/Originality of this study: The novelty of this research lies in the validators who validated this E-LKPD so that it can be developed into a better product using CVR and CVI.